1998
DOI: 10.1080/026990598122430
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a family member with a traumatic brain injury

Abstract: The responses to a questionnaire on subjective burden are reported for 52 primary caregivers of a group of persons with traumatic brain injuries sustained an average of 6 years previously. The aim of the study was to examine satisfaction with social support, perception of coping skills, and appraisal of symptoms as predictors of strain in the carers. A range of responses, both positive and negative, to the work of caring for a relative with a head injury was reported. A high prevalence rate of emotional and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 27 publications
1
80
0
17
Order By: Relevance
“…A poor social network has been previously shown to predict caregiver burden; caregivers with a high burden 1 year post-injury were more lonely and met with friends and family less frequently . Although one study found no relationship between caregiver burden and lack of a social network (Knight et al, 1998), others have demonstrated that a lack of perceived social support was related to a higher caregiver burden (Hanks et al, 2007;Kreutzer et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A poor social network has been previously shown to predict caregiver burden; caregivers with a high burden 1 year post-injury were more lonely and met with friends and family less frequently . Although one study found no relationship between caregiver burden and lack of a social network (Knight et al, 1998), others have demonstrated that a lack of perceived social support was related to a higher caregiver burden (Hanks et al, 2007;Kreutzer et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Dans ce contexte, la famille représente généralement la première source de support de la victime (Hawley, Ward, Magnay & Long, 2003;Knight, Devereux & Godfrey., 1998;Kreutzer, Gervasio, & Camplair, 1994a, 1994b. La famille ou les proches aidants doivent composer avec les séquelles psychologiques, comportementales et cognitives, entre autres au niveau des fonctions executives, qui sont consécutives à la blessure cérébrale de leur proche, ce qui risque d'induire un stress en lien avec la demande adaptative que la situation impose aux aidants (Katz, Zasler & Zafonte, 2007;Sander, 2007).…”
Section: XIVunclassified
“…L'impact différentiel relatif de ces deux aspects serait toutefois difficile à estimer. Pour de nombreux auteurs, les troubles de l'axe 1 (DSM-IV) les plus fréquemment diagnostiqués sont : la dépression et l'anxiété (Evered, Ruff, Baldo & Isomura, 2003;Knight et al, 1998;Truelle, Fayada, & Montreuil., 2005). Selon Ponsford et al (2008), l'importance de ces troubles tend à demeurer stable sur une période de dix ans.…”
Section: Les Impacts Comportementaux Et Psychopathologiques Directs Ounclassified
See 2 more Smart Citations